A formação do professor de ensino religioso dos anos iniciais: conversas sobre o Ântropos, Thréskeia e Epistême - Saucedo, Kellys Regina Rodio (2015)
The last decade of the twentieth century was an important period for the reformulation of the legislative corpus regarding Religious Education in Brazil. In the history of the discipline, there has been the predominance of optional registration with mandatory offer in the curricula of public elementary schools. Nevertheless, despite this characteristic, the State delegated to volunteers, generally linked to religious institutions, the responsibility for teaching the subject. With the enactment of the Federal Law nº 9475/1997, which amended what was stated in the article 33 of the LDB (Law of Guidelines and Bases of Education) in force, the expression “at no cost to the state” was removed from this federal law, and education systems began to regulate the hiring of teachers. In the state of Paraná, the Deliberation nº 01/2006 of the State Board of Education indicates, as selection and hiring criteria for the Religious Education in the early years, primarily, the option for graduates in Pedagogy. This guideline led to the following central research question: how the pedagogues are being prepared to teach Religious Education? In order to answer this question, three instruments were used: literature review, documentary research and field research. Literature review aimed to cover the historical background of Religious Education and the presence of Religion in the History of Brazilian Education. These data provided relevant information underpinning the main issues on initial formation and the performance of Religious Education teachers. More specific readings on different historical contexts were also included, showing how the relationship between Science and Religion had – and sometimes still have – different impacts on society. It is understood that, directly or indirectly, these debates interfere with the teacher’s initial education and performance, with implications in the classroom that can contribute or not to the development of children in early learning processes. Documentary research was carried out through the analysis of laws, rules, instructions and other official documents produced by the national, state and municipal legislative and regulatory bodies designed to organize the subject of Religious Education. Field research was constituted by interviews with four coordinators of Education (Pedagogy) in-classroom courses of Higher Education Institutions from Cascavel (Paraná, Brazil) and by a questionnaire applied to senior students of these courses, which propitiated to apprehend the mismatches of initial education related to the teaching of Religious Education. With respect to the Municipal School System, interviews were carried out with the Municipal Coordinator of Religious Education, fourteen Religious Education teachers and a school director. The results indicate that the nature of the production of religious knowledge and the influence of Religion in child development are underemphasized content both in initial and in continuing education of teachers. Another important result of this study was the finding that the sample participants generally have serious shortcomings in their education with regard to constructing conceptual overviews of Science and Religion topics. Research data also highlighted the need to rethink the initial and continuing education of Religious Education teachers, because the current legislation has not been sufficient to elucidate the problem regarding the content approach and, in some cases, the materialization of the current epistemological proposal of Religious Education. In this sense, the suggestion is to include, in the initial and continuing education of pedagogues, discussions on the history of the discipline and the methodological and epistemological differences of the nature of religious and scientific knowledge, considering that these contents are the basis to build dialogical bridges with other areas of knowledge, including the teaching of Science.